OPTIMASI FORMULA DAN UJI EVALUASI FISIK SEDIAAN ESSENCE KOMBUCHA DENGAN VARIASI KONSENTRASI PROPYLENGLIKOL DAN GLISERIN - Ayu Ningrum, Yuyun Darma; Sholeh, Aries Badrus; Ramadhini, Amelianingrum (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
Skin problems can be treated with several cosmetic products such as essence. Essence is a skin care product that is part of skincare. Essence is a cosmetic product that has added value and optimal effects, namely as a humectant, ultraviolet protector, whitening agent, antioxidant, anti-inflammatory and skin rejuvenator. This Research using experimental method and aims to determine the optimal concentration of propylene glycol and glycerin in the optimum preparation of kombucha essence. In the results of the SLD method, 28 solutions were obtained, then for formula optimization the composition ratio between Propylene glycol and Glycerin was chosen as 11.5: 8.25 with a desirability value of 1.00. The resulting predicted values ??are a pH test of 5.255 and a viscosity test of 546.7. The analysis used a parametric sample t-test which showed that the results were not significantly different. This is shown by the value (p>0.05), so the results above indicate that the kombucha essence formula before and after the stability test was carried out obtained stable pH and viscosity values ??during storage based on the parametric sample t-test. The research results showed that the essence preparation made had an optimal formula in formula 3, namely transparent white, had a pH within the range so it was safe for the skin, was homogeneous and a viscosity value of 528.7 cp.